Design of the Coal Mining Transient Electromagnetic Receiver with A Large Dynamic Range - Xiaoliang Zheng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Considering the influence of the transient process of transient electromagnetic receiving coil on the early signals detection of the secondary field, as well as the great change and the various decay rates in different periods of the secondary field signals, which will affect the secondary field signal collection, we aim at designing a new receiver with the variable stored program control receiving coil, prefixed amplifying circuit, programmable amplifying circuit and high-performance analog-to-digital conversion circuit according to the underground coal mining environment, in which we apply the different sampling interval software and self-adaptive filtering algorithm to eliminate the influence of transient process and filter out the 50Hz power line interference, thus to increase the data collection ability and improve the detection result. The whole device is suitable for underground coal mining environment with a small volume.